Global Trends in Internal Control and Public Sector Accounting Fraud Research: A Bibliometric Study - Darmawati,; Elis Mediawati,; Andi Ratna Sari Dewi , (Asian Journal of Business and Accounting, 2026)
Manuscript type: Literature review Research aims: This research aims to review global trends in the topic of internal control and accounting fraud in the public sector using a bibliometric approach to identify patterns, developments, and gaps in the available literature. Design/Methodology/Approach: This study used bibliometric analysis of databases such as Scopus and Emerald to explore trends in “internal control and public sector accounting fraud”, involving literature selection based on keywords, data filtering, and processing using Biblioshiny R-Studio and VOSviewer for collaborative and thematic analysis and visualisation. Research findings: Public sector accounting fraud and internal control research during 2018-2023 revealed a major focus on ‘fraud’, ‘corporate governance’, and ‘internal control’, with 473 papers predominantly authored by a relatively small group of contributors. This trend reflects a global response to emerging issues such as regulatory reforms and the impact of pandemic, underscoring the importance of international collaboration and the growing role of academic institution in addressing public sector accountability. Theoretical contribution/Originality: This research makes a theoretical contribution by using bibliometric analysis to uncover trends and dynamics in “internal control and public sector accounting fraud”, highlighting the role and impact of international collaboration and the influence of global factors in the field. Practitioner/Policy implication: This research emphasises the importance of adopting more effective internal controls and strong governance within the public sector to prevent fraud, providing practical insights for practitioners and policymakers. In addition, the findings suggest the need for international collaboration and policy adaptation to global changes such as the pandemic, to improve transparency and accountability.